Effects of Ceftriaxone on Glial Glutamate Transporters in Wistar Rats Administered Sequential Ethanol and Methamphetamine - Althobaiti, Yusuf S.; Alshehri, Fahad S.; Almalki, Atiah H.; Sari, Youssef (Frontiers in Neuroscience, 2016)
Methamphetamine (METH) is one of the psychostimulants that is co-abused with ethanol. Repeated exposure to high dose of METH has been shown to cause increases in extracellular glutamate concentration. We have recently reported that ethanol exposure can also increase the extracellular glutamate concentration and downregulate the expression of glutamate transporter subtype 1 (GLT-1). GLT-1 is a glial transporter that regulates the majority of extracellular glutamate. A Wistar rat model of METH and ethanol co-abuse was used to examine the expression of GLT-1 as well as other glutamate transporters such as cystine/glutamate exchanger (xCT) and glutamate aspartate transporter (GLAST). We also examined the body temperature in rats administered METH, ethanol or both drugs. We further investigated the effects of ceftriaxone (CEF), a β-lactam antibiotic known to upregulate GLT-1, in this METH/ethanol co-abuse rat model. After 7 days of either ethanol (6 g/kg) or water oral gavage, Wistar rats received either saline or METH (10 mg/kg i.p. every 2 h × 4), followed by either saline or CEF (200 mg/kg) posttreatment. METH administered alone decreased GLT-1 expression in the nucleus accumbens (NAc) and prefrontal cortex (PFC) and increased body temperature, but did not reduce either xCT or GLAST expression in ethanol and water-pretreated rats. Interestingly, ethanol and METH were found to have an additive effect on the downregulation of GLT-1 expression in the NAc but not in the PFC. Moreover, ethanol alone caused GLT-1 downregulation in the NAc and elevated body temperature compared to control. Finally, CEF posttreatment significantly reversed METH-induced hyperthermia, restored GLT-1 expression, and increased xCT expression. These findings suggest the potential therapeutic role of CEF against METH- or ethanol/METH-induced hyperglutamatergic state and hyperthermia.